Data Encryption and Decryption Algorithms using Key Rotations for Data Security in Cloud System (International Journal of Engineering and Computer Science, 2014)
Outsourcing the data in cloud computing is exponentially generating to scale up the hardware and software resources. How to protect the outsourced sensitive data as a service is becomes a major data security challenge in cloud computing. To address these data security challenges, we propose an efﬁcient data encryption to encrypt sensitive data before sending to the cloud server. This exploits the block level data encryption using 256 bit symmetric key with rotation. In addition, data users can reconstruct the requested data from cloud server using shared secret key. We analyse the privacy protection of outsourced data using experiment is carried out on the repository of text ﬁles with variable size. The security and performance analysis shows that the proposed method is highly efﬁcient than existing methods performance.